Immediate Targeted Nipple–Areolar Complex Reinnervation: Improving Outcomes in Gender-affirming Mastectomy. Issue 3 (24th March 2020) - Rochlin, Danielle H.; Brazio, Phil; Wapnir, Irene; Nguyen, Dung
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Female-to-male mastectomy often renders the chest skin and nipple–areolar complex (NAC) insensate. We propose a new technique of preserving the intercostal nerves and using them to reinnervate the NAC after mastectomy. Methods: We performed a prospective analysis of transmasculine patients who underwent female-to-male mastectomy. The technique involves dissecting out the lateral intercostal nerves to length and performing a neurorrhaphy to nerve stumps at the base of the NAC. Sensory outcomes, as assessed with Semmes–Weinstein monofilaments, were compared to a cohort of patients who underwent mastectomy without neurotization. Results: Ten patients with a mean age of 17.5 years (range: 16–19 years) underwent mastectomy. The final follow-up was a mean of 15.4 ± 4.3 months for the treated group and 40.7 ± 12.9 months for the control group. Compared to control patients, treated patients had significant improvement in sensation at the nipple ( P ≤ 0.0002), areola ( P = 0.0001), and peripheral breast skin ( P = 0.0001). For treated patients, there was no statistically significant difference in sensation between preoperative and postoperative sensation in all tested areas at final follow-up. Conclusion: This proof of concept study suggests that immediate reinnervation of the NAC after mastectomy enhances recovery of NAC sensation in patients undergoing female-to-male mastectomy and may be further generalized to women undergoing postmastectomy breast reconstruction.